Konsep Mahabah Jalaluddin Rumi dan Relevansinya dengan Pelestarian Lingkungan - Al Fitra Ghulam Waffa Safiro; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the concept of mahabah according to Jalaluddin Rumi and its relevance to environmental preservation. The research method used is a qualitative type through literature study. The results and discussion of this study are that there is a concept of love in society that has experienced a reduction in meaning which makes it so narrow. This is due to the lack of public understanding of the concept of mahabah which is often referred to as